2002
DOI: 10.1017/s0021932002004078
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Age at Marriage Influence Gynaecological Morbidities Among Pakistani Women?

Abstract: This paper presents the prevalence of and investigates predictors for specific perceived gynaecological morbidities in Pakistani women. A total of 717 women were identified from eight squatter settlements in Karachi, Pakistan. Detailed information on demographics, contraceptive use and gynaecological morbidities was elicited. The perceived prevalence of uterine prolapse was 19·1% and that of pelvic inflammatory disease 12·8%. The prevalence of uterine prolapse (adjusted odds ratio 1·8; 95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Women who began sexual activity in their teens, as compared to women who started after 25 years of age, reported a greater burden of reproductive ill-health. This affirms the risks associated with early marriage and the need to improve and broaden reproductive health services and education [11]. In an earlier study the authors interviewed newly married young women in the same slum area about their experiences of marriage.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Women who began sexual activity in their teens, as compared to women who started after 25 years of age, reported a greater burden of reproductive ill-health. This affirms the risks associated with early marriage and the need to improve and broaden reproductive health services and education [11]. In an earlier study the authors interviewed newly married young women in the same slum area about their experiences of marriage.…”
Section: Introductionmentioning
confidence: 67%
“…The submission described by participants was instilled in the young women through the impact of diverse levels of the family, community and society on their lives: their parents deciding about their marriage, often without their consent, the extensive demands placed on them by their parents-in-law and the pervasive societal expectations for them to be obedient in all spheres of life. Many of the difficulties young women experience are related to societal beliefs and expectations that make them more vulnerable to reproductive ill health [11,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study from Pakistan reported a prevalence of 19.1% 15 , while another community based survey in rural Gmbia reported a much higher rate of 46%. Even much higher prevalence of 64.6% was reported from a recent rural Tanzania study 1 .…”
Section: Discussionmentioning
confidence: 85%
“…Many find themselves socially isolated and with poor inter-spousal communication [ 2 , 3 ]. Adolescent marriages lead to early pregnancies and complications due to immaturity contributing to their vulnerability [ 4 ].…”
Section: Introductionmentioning
confidence: 99%